The Correlation between Reading International Journal Articles on Enriching the University EFL Students’ Academic Vocabulary - Lestari, Susiyanti; Dj, Muhammad Zuhri; Hasanah, Uswatun (International Journal of Research on English Teaching and Applied Linguistics, 2023)
The purpose of this research was to investigate the correlation of reading international journal articles on enriching students' knowledge of academic English vocabulary. This research used a quantitative method with correlation analysis and used non-random sampling to determine the sample from the population. The data of this research was obtained through questioner which consisted of 15 statements to collect the data of students' reading activity (X). Besides, the dependent variable (Y) was enriching students' knowledge of academic English vocabulary collected by using a test (multiple-choice) that consisted of 20 questions about vocabulary mastery knowledge. The participants of this research were 31 seventh-semester IAIN Bone students. Furthermore, the data collected was analyzed by using Pearson’s correlation analysis with SPSS version 25. The result of this study showed that there was significant correlation between reading international journal articles in enriching university EFL students’ academic vocabulary. It proved with the result of coefficient correlation test that showed the sig.(2-tailed) was .000 < .05 and the value of Pearson correlation was .822 that could be assumed it has large of degree of correlation. It also interpreted that H0 was rejected and H1 had accepted means there was a positive and significant correlation.